2010
DOI: 10.2478/v10038-010-0015-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Intensities of Flexibility Training on Explosive Force

Abstract: Purpose. To verify whether there are changes in the performance levels of the explosive force when the same muscle group previously under went different intensities of flexibility training (stretch & flex). Basic procedures. The tests were performed with 25 females on three consecutive days and were preceded by a 10minute warmup period. First, each participant performed a maximum vertical jump on a contact platform. The jump was repeated after 10 minutes, and the first day was considered the control (C). On th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…This review analysed the effects of different stretching in the warm-up on physical performance variables such as jump height in CMJ and ROM. Fourteen of the included articles analysed the CMJ [38][39][40][41][42][43][44][45][46][47][48][49][50][51] and five analysed the ROM [39,41,50,52,53]. The characteristics of the participants are summarised in Table 1.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…This review analysed the effects of different stretching in the warm-up on physical performance variables such as jump height in CMJ and ROM. Fourteen of the included articles analysed the CMJ [38][39][40][41][42][43][44][45][46][47][48][49][50][51] and five analysed the ROM [39,41,50,52,53]. The characteristics of the participants are summarised in Table 1.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Studies in which participants were advised to hold the stretch less than 20 s (Carvalho et al, 2012;Dalrymple et al, 2010;Galdino et al, 2010;Gonzalez-Rave et al, 2009;Kinser et al, 2008;Murphy et al, 2010; did not result in significant effects on any of the jump performances. Thus, hold time for static stretches should be standardized to 20-30 s. The stretch can be performed actively or passively depending upon the situation and requirements.…”
mentioning
confidence: 84%
“…The control group, who only performed 10 min of treadmill exercise, and the static dynamic stretching group, who performed two repetitions of a full ROM while walking on an indoor court, had more improvement in countermovement jump height Chaouachi et al (2010). concluded that static stretching to the point of discomfort or slightly less than to the point of discomfort does not affect the height of the countermovement jump, performed with a self-selected comfortable countermovement height Galdino et al (2010). concluded that stretching, held for 10 s at the end of normal ROM, significantly reduced countermovement jump height, with the jump performed with the hands on the hips Tsolakis et al (2010).…”
mentioning
confidence: 98%
See 2 more Smart Citations